(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Field experiment was conducted in the non-heated plastic house at Al-Mussaib Technical College in the autumn season 2016 to study the Response of sweet pepper Capsicum annuum L. (Qurtuba cultivar) to foliar spraying with two types of foliar commercial Potassium fertilizers in loamy sand soil. To study the effect of four levels of potassium fertilizer and micronutrients (0, 4, 6, 8 ml.L-1), four levels of potassium fertilizer and Sulfur KTS (0, 2, 4, 6 ml.L-1) and their interaction on some vegetative and flowering growth indicators, yield and its components. The experiment was designed according to the Randomized Complete Block Design (RCBD) and the averages were compared with the least significant difference (LSD), with a significant level of 5%. The result indicated to the excelling of the spraying treatment with potassium and micronutrient (8 ml.L-1) by giving it a significant level in increasing the averages of plant height, number of branches, leaf area, dry weight for total vegetative, number of flowers in plant, percentage of fruit set, the leaves content of (chlorophyll, nitrogen, Phosphorus and potassium), early and total yield, the content of vitamin C, and percentage of Total Soluble Solids, with an increasing percentage of (19.47, 29.54, 16.68, 30.01, 11.26, 24.09, 38.16, 24.36, 16.67, 34.00, 21.87, 20.27, 50.46, 45.96, 39.33, 70.85%), respectively, compared to control treatment. Which is the same behavior as spraying treatment with potassium fertilizer and sulfur, where treatment (4 ml.L-1) was excelled in all the above traits, where the percentages of increasing were (31.72, 53.53, 49.88, 15.82, 14.84, 24.54, 19.79, 36.73, 21.05, 47.55, 24.53, 19.07, 49.43, 48.01, 30.29, 36.56%), respectively, compared to the control treatment. As for interaction treatments, it has showed excelling the spraying treatment with a mixture of (8 ml. L-1 + 4 ml. L-1) by giving it the highest values for all the above traits amounted of (109.5 cm, 6.4 branches, 25.3 dm2, 132.7 g, 62.7 flower, 43.9% 2.22%, 0.75%, 2.55%, 34.6 fruits, 108.3 g, 0.790 kg. plant-1, 3.747 kg. plant-1, 69.2 mg.100 ml-1, 10.4%), respectively.